2013
DOI: 10.5455/cap.20130531
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Alexithymia

Abstract: ÖZET"Duygular için söz yokluğu" anlamına gelen ve psikiyatri çevrelerince hızla kabul görmüş bir kavram olan aleksitimi, başlangıçta psikosomatik hastalardaki belirtileri açıklamak için ortaya atılmıştır. Ancak güncel çalışmalar aleksitiminin birçok farklı patolojik grupta ve hatta sağlıklı popülasyonda da karşımı-za çıkan bir kişilik özelliği olabileceğini ortaya koymuştur. Bu noktada aleksitimi kavramının var olan yapı ve tanılardan ayrılması ve gerek kuramsal gerekse ölçümsel anlamda güvenirlik ve geçerliği… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 90 publications
1
10
0
8
Order By: Relevance
“…Alexithymia is not a condition that is only seen in organic, psychiatric, or psychosomatic diseases. Alexithymic features may also be seen in general population 17,18. Various studies reported the prevalence of alexithymia (20-item Toronto Alexithymia Scale [TAS-20] total score, ≥61) to be between 12% and 18%.…”
Section: Introductionmentioning
confidence: 99%
“…Alexithymia is not a condition that is only seen in organic, psychiatric, or psychosomatic diseases. Alexithymic features may also be seen in general population 17,18. Various studies reported the prevalence of alexithymia (20-item Toronto Alexithymia Scale [TAS-20] total score, ≥61) to be between 12% and 18%.…”
Section: Introductionmentioning
confidence: 99%
“…The biomarkers of urea, creatinine, hemoglobin, hematocrit, albumin, sodium, potassium, calcium, phosphorus, and C-reactive protein (CRP) values of the subjects who participate in the study were evaluated. The median number of medications used by the patients on a daily basis was three (min-max: [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Normally deviating values were determined and the relationship between the HSS, HSS subscales, TAS-20, and TAS-20 subscale scores was assessed.…”
Section: Resultsmentioning
confidence: 99%
“…6 Alexithymic behavior patterns observed in patients have been defined as: nervousness, short temperedness, touchiness, introversion, loss of interest and desire, loss of hope for the future, distress, anxiety and emotional deprivation as a result of these. 5,7 Feelings such as fear, anger, and sorrow in alexithymic individuals create a loss in persuasive properties and may cause individuals to mask their emotions in some way. 8 It has been observed that alexithymia studies in the literature are primarily concentrated on psychiatric diseases.…”
mentioning
confidence: 99%
“…It should be noticed that, alexithymic signs are not absolutely pathological. They may also be seen in general population to some extent 6,7 . Various research reported the prevalence of alexithymia (TAS-20 total score ≥ 61) to be between 12 and 18%, besides, results about gender differences were contradictory 8,9 .…”
Section: Introductionmentioning
confidence: 92%